Radikalni konstruktivizem in sistemska teorija kot teoretična temelja empirične literarne znanosti - Dović, Marijan (Primerjalna književnost, 2002)
Radical constructivism and systemic theory as theoretical grounds of empirical literary studies. On the basis of an extensive theoretical background, also provided in this article, empirical literary studies (ELS) developed a specific concept of a literary system and a theoretical-methodological apparatus. The article deals with radical constructivism, which has developed as a new epistemological and cognitive paradigm, and a systemic theory, which offers a framework for the interpretation of a literary system and its status in contemporary science.
Keywords: literary science; literarna veda; metodologija; literarni sistemi; radikalni konstruktivizem; sistemska teorija